When Congress Makes a Joke: Congressional Humor Then and Now - Yarwood, Dean L. (Rowman & Littlefield Publishers, 2004)
When Congress Makes a Joke is an engaging look at the intentional use of humor by members of Congress, exploring their humor as political communication. Highlighting several politicians noted for their use of humor—including Senators Robert Dole and Alan Simpson and Representatives Patricia Schroeder and Barney Frank, among others—this intriguing book features original personal interviews with the Congress members, allowing them to talk about their own (and others') use of humor in political ways. Yarwood also includes theories of humor as communication, a historical look at humor in Congress, the function of telling humorous stories, and the role of humor in the integration of African American and women members into the institution of Congress. Readers will find When Congress Makes a Joke an enjoyable, accessible view into humor's place in political communication—how it is created, how it is used, and what consequences may stem from it.